RENIN SINGLE-NUCLEOTIDE POLYMORPHISM (rs5705) IN HEALTHY INDIAN POPULATION - Varakantham, Varsha; Venkata, Manjula; Bharatraj, Dinesh Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Renin gene (REN) polymorphisms are studied to understand its association with different diseases such as hypertension. The genetic variants have different frequencies in various populations. Therefore, we have established normal frequencies of rs5705 variants in healthy Indian population. Methods: The genotype and allele frequencies of rs5705 were determined in 324 healthy Indian population using real-time polymerase chain reaction. Results: Our study showed 91.7% T allele or TT genotype and 8.3% G allele or TG genotype. It is interesting to note that the minor allele (G) is found only in the form of heterozygous TG condition and the homozygous form GG was absent. These frequencies were compared with different populations. Conclusions: The significant variations found between our population and others confirm interethnic variations. Future studies may use our established genotype frequencies of rs5705 to understand the risk of diseases such as hypertension.